Development And Evaluation Of The Home Pharmacy Asthma Care (Hom-Pac) Programme Among Adult Patients With Asthma From Kulim Hospital, Kedah, Malaysia - Ramadoo@Devudu, Jaya Muneswarao (2021)
Asthma control among adult patients in Malaysia is unsatisfactory. Several guidelines have recommended home care interventions as part of asthma management strategies. The evidence of home-based care in improving asthma outcomes is well established in the paediatric population but limited among adults. To date, there are no published studies that evaluated the effectiveness of pharmacist-led home care interventions, specifically in adult asthma patients. The Home Pharmacy Asthma Care (HOM-PAC) programme was developed to enable pharmacists to provide comprehensive home-based care for adult asthma patients. Therefore, the present study aimed to develop and evaluate the effectiveness of the HOM-PAC programme in patients with asthma. A two-arm, 6-month, open-label, parallel-group, randomised controlled trial (RCT) was conducted. Patients with uncontrolled asthma symptoms were recruited from the adult respiratory clinic of Kulim Hospital, Kedah. The patients were assigned to either the intervention (HOM-PAC programme) or control (usual care) groups based on a pre-generated random list. A total of three visits (3 months apart) were planned for patients in the intervention group. The patients in the control group did not receive the HOM-PAC intervention and continued their regular clinic follow-ups. Fifty-one patients in the intervention group and 54 patients in the control group completed the study and were included in the final analysis.